The influence of training, job interest, and job environment on employee performance at PT. Tanina Karya Ajiborna - Yufriser Pasaribu; Andre Fitriano; Rody Syafrizal (Journal of Economics and Business Letters, 2023)
In achieving the goals of organization, it requires good human resources to manage the system. In order for this system work, several important aspects must be considered, such as training, work interest, and work environment. The purpose of this training to analyze the effect of training, work interest, work environment on the performance of employees of PT. Tanina Karya Ajiborna. Research method used is quantitative research, where variables are measured using Likert scale. Methods of data collection was by interview (interview). Population in this study amounted 112 people.total sample of 89 people. Data processing using SPSS software with descriptive analysis and hypothesis testing multiple regression analysis. The results showed that the Partial Test (T test) using the SPSS test on Training had a significant value (0.567) and t count (0.168) H1 was accepted, meaning that XI had an effect on Y. In Job Interest it was known that it had a significant value (0.039) and t count (2.101) it can be concluded that XI has an effect on Y. Through the Partial Test (T test) SPSS testing on the influence of the Work Environment on Employee Performance significant value (0.678) and t count (0.417) H1 is accepted, X1 has an effect on Y. By conducting a Simultaneous Test (F test) using SPSS on the effect of variable X on Y. Then it is known that F count is 0.739 > F table 2.71 or a Sig of 0.532 which means H0 is rejected and ha is accepted